2019
DOI: 10.1002/app.48571
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ion substituted alginate‐based hydrogel fibers and its coordination binding model

Abstract: Sr-alginate and Ca-alginate hydrogel fibers were fabricated via microfluidic spinning technology, and various analytical methods were adopted to characterize fibers and disclose the coordination model of Sr 2+ binding with alginate molecule chain. For both fibers, the more crosslinking sites of Sr 2+ with alginate molecule were illustrated in comparison with that of Ca 2+ . The more robust mechanical performance of Sr-alginate fibers than Ca-alginate counterpart was a strong indication of the more strong bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…However, the poor mechanical properties of the calcium alginate microfibers can limit their application in tissue engineering. Recently, Sr 2+ was demonstrated that had more crosslinking cites with alginate molecule than that of the Ca 2+ , which further resulted in the fabrication of microfibers with more robust mechanical performance [ 95 ]. Besides, the mixture of carbon nanotubes and sodium alginate solution were used as core flow, and the resultant microfibers exhibited ultrahigh mechanical strength [ 96 ].…”
Section: Nano/micro-fibers Fabrication Techniquesmentioning
confidence: 99%
“…However, the poor mechanical properties of the calcium alginate microfibers can limit their application in tissue engineering. Recently, Sr 2+ was demonstrated that had more crosslinking cites with alginate molecule than that of the Ca 2+ , which further resulted in the fabrication of microfibers with more robust mechanical performance [ 95 ]. Besides, the mixture of carbon nanotubes and sodium alginate solution were used as core flow, and the resultant microfibers exhibited ultrahigh mechanical strength [ 96 ].…”
Section: Nano/micro-fibers Fabrication Techniquesmentioning
confidence: 99%
“…Zhang et al prepared Ca and Sr-alginate fibers with microfluidic spinning technology, and verified that the chelation type of Sr 2+ with alginate being similar to that of Ca 2+ , i.e., core-shell of the analogous egg-box structure. Compared to Ca-alginate counterpart, there were more crosslinking sites of Sr 2+ with alginate molecule, which resulted in higher crosslinking degree and stronger binding of Sr 2+ with alginate molecular chain, hence more robust mechanical performance of Sr-alginate fibers [ 22 ]. Cation charges may also affect the gel properties.…”
Section: Compositions Structures and Propertiesmentioning
confidence: 99%
“…Strontium (Sr) is structurally, physically and chemically similar to calcium. It has been proved to have treatment effect on osteoporosis, thus become another commonly selected ion for alginate hydrogel [ 22 ]. As long as Sr only has stable isotopes (naturally occurring), the health risk is minimal.…”
Section: Preparation and Processing Technology Of Alginatesmentioning
confidence: 99%
“…However, herein they did not deeply study the detailed coordination mechanism of large radius metal-ion ions. In order to gain further understanding for this, Zhang et al prepared the strontium (Sr) with a large radius and Ca ions cross-linked Alg hydrogel fibers, and found that the bonding ways between Sr 2+ or Ca 2+ and Alg were similar, just more ether oxygen involved in bonding with Sr 2+ , leading to a higher degree of cross-linking at the same charge ratio. Therefore, for alkali metal ions, the higher the valence state, the more anions on polymer chains will participate in ion bonding, and as the radius of metal ions increases, the functional polar groups such as ether will coordinate with metal ions, both of which result in a higher degree of cross-linking.…”
Section: Recent Advances Of Cbcbsmentioning
confidence: 99%